Efforts to Improve Science Learning Achievement of Grade IX A Students of SMP Negeri 3 Sewon Using the Multy Representacy (DMR) Discourse Model for the 2021/2022 Academic Year - Sarjito Sarjito (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to improve natural science (IPA) learning achievement using the Multy Reprecentacy (DMR) Discourse learning model.  This study is a class action research conducted with two (2) cycles. Each cycle consists of three (3) meetings, namely two (2) meetings for the learning process and one (1) meeting for achievement tests that are done independently. Each cycle follows the stages of the Kemmis and Taggart model which includes four components: planning, action, observation and reflection. The data collected in this study is the result of research related to the implementation of learning using the Multy Reprecentacy (DMR) Discourse model on natural science (IPA) material. Data collection techniques use test and non-test techniques with descriptive and qualitative approaches. The results showed that the use of the Multy Reprecentacy (DMR) Discourse model in natural science learning activities can improve student achievement. This increase in prestige is the effect of better and conductive teaching and learning activities of teachers and students. The success of this increase in learning achievement can be seen from the increase in learning achievement scores after conducting achievement tests with the "Multy Reprecentacy (DMR) Discourse" model, compared to learning using the lecture method. So learning using the "Multy Reprecentacy (DMR) Discourse" model, is proven to increase the achievement of science (science) for junior high school students.